Women perspective of shifting paradigms towards online shopping. Issue 7 (3rd October 2022) - Singh, Nisha; Bhatia, Archana
Abstract: Online shopping is a method of purchasing goods and services from the comfort of one's own home, office, or any other location with internet access. It is the shifting paradigm of offline to online shopping scenario, specially in the Covid era when everybody in the whole world were forced to stay at their homes to be safe and movement was allowed only to buy groceries for stipulated period. The purpose of this study is to analyze the shifting paradigm of shopping from offline to online from the women perspective. The judgmental non probability sampling approach was used to gather cross-sectional primary data from online and offline women shoppers of the country. The questionnaire is prepared with the help of a literature review and experts. In order to understand the preferences of customer, discriminant analysis is applied on the collected responses of 200 women customers from metro cities of the country using SPSS software. The response data consists of the ratings provided by the women consumers for the different mode of shopping. It is compared with the help of Descriptive Statistics, Discriminant Analysis, Wilks Lambda, F stats and its p value. In the study the fifteen attributes are considered for comparing the preferences of women for shopping and found that out of fifteen attributes eight attributes are considered by women customers for online shopping, six for offline and in one attributes their preferences for online and offline shopping is almost same.